A selection of american folktales to teach english through interactive activities for teenagers - Dávila Toro, Omar (2011)
This investigation is about the use of folktales as a tool to teach English to teenagers. Its scope considers the interaction of students through technology, specifically with media. The technique is called digital storytelling. To develop a story it is recommended to use Microsoft PowerPoint, Word and Adobe Flash Player. They are easy to use throughout the combination of images, words, voices and audio.